ANALYSIS OF MENTAL WORKLOAD ON WORKERS IN SERVICE DEPARTMENT USING THE NASA-TLX METHOD - Aryo Putro Satriyono, Raden Danang; Putri, Arinda Soraya; Rizkan Bakhtiar , Muhammad (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2023)
CV. Istiqomah Furniture is a company engaged in manufacturing furniture located in Klaten, Central Java. The problems that are often faced by CV. Istiqomah Furniture, namely the decrease in worker productivity and the number of final products that are not following company standards. One of the departments responsible for these problems is the service department. The high intensity of work in the service department can cause a mental burden for workers. The purpose of this study is to calculate the mental workload felt byworkers, find out the dominant factors that cause this mental burden, and provide alternative improvements based on the problems faced by the company. The method used in this research is NASA-TLX (National Aeronautics and Space Administration Task Load Index). The results of this study are that the average worker has a high mental workload with a WWL value of 72.11, and the mostinfluential factors are physical and mental needs. Based on these results, the proposed improvements provide sufficient rest time, improve worker safety and comfort, increase work motivation, provide adequate facilities, conduct medical tests, and provide good nutrition.